Genome Survey of Chromatin-Modifying Enzymes in Threespine Stickleback: A Crucial Epigenetic Toolkit for Adaptation? - Fellous, Alexandre; Shama, Lisa N. S. (Frontiers in Marine Science, 2019)
Ocean environments are changing rapidly and marine organisms need to cope with these changes in order to survive, develop and reproduce. To do so, organisms can either migrate, adapt in situ or acclimate via phenotypic plasticity. In this context, the emerging field of environmental epigenetics investigates the contribution of genetic and epigenetic information to adaptive potential of wild populations. Epigenetic modifications are based on the highly dynamic combination of DNA methylation, histone modifications and non-coding RNAs, which may facilitate phenotypic plasticity through genotype-epigenotype-environment interactions, and can drive rapid evolution in wild populations. However, while knowledge of epigenetic contributions to phenotypes across different developmental and generational timescales is increasing for medical research model species, the mechanistic and synergistic action of these modifications remain comparatively understudied in ecological models such as teleost fishes. Here, we characterized the evolution of the gene toolkit involved in key molecular epigenetic pathways including DNA methylation, histone modifications, macroH2A histone and miRNA biogenesis/turnover in threespine stickleback, a model species in evolution and ecology. We then investigated these genes within a phylogenetic context by comparing them in stickleback to human, mouse, chicken, tropical clawed frog, zebrafish, medaka, green spotted puffer, channel catfish and mangrove rivulus. We found that, in general, conserved domains, in conjunction with their phylogenetic positions, suggest evolutionary conservation of putative enzyme activity in stickleback. However, molecular epigenetic pathways also revealed that teleost gene evolution is diversified and complex. Specifically, the number of genes, gene loss/duplication events, identified conserved domains, and putative protein lengths vary greatly from one species to another, particularly within fishes, which exhibit a potentially new class of histone deacetylases. This suggests different biological functions specific to fish species, and that the action of genes regulating epigenetic modifications in model species are not necessarily applicable to other related species. We integrate our results into recent advances concerning epigenetic mechanisms in teleosts, and conclude by discussing the necessity to delve deeper into the fundamental mechanics of epigenetic modifications in a wide array of taxa, particularly those relevant for assisted evolution, conservation, aquaculture, fisheries, and climate change-adaptation studies.